GE_GERICHTE A/939/2014 vom 26. Juni 2014 - GE Cour de justice (2014)
Famille du poursuivi; Preuve de l'état civil; Copie de pièces; Avis aux débiteurs. | Plaintes rejetées. | LP.93.1; CC.285.2bis; CC.291